2020
DOI: 10.3390/genes11060601
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of bta-miR-210 in Bovine Early Intramuscular Adipogenesis

Abstract: Intramuscular fat (IMF) is one of the major factors determining beef quality. IMF formation is influenced by multiple conditions including genetic background, age and nutrition. In our previous investigation, bta-miR-210 was found to be increased during adipogenesis using miRNA-seq. In this study, we validated the upregulation of bta-miR-210 in platelet-derived growth factor receptor α positive (PDGFRα+) progenitor cells during adipogenic differentiation in vitro. To investigate its role in adipogenesis, bta-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Advancements to high-throughput sequencing technology has allowed deeper exploration of cellular regulatory processes (Katz et al, 2010 ). Previous studies have already revealed the regulatory effects of human miRNA, including miR-204 (Zhang Z. et al, 2020 ), miR-27a (Kim et al, 2010 ), miR-210 (Ren et al, 2020 ), miR-24 (Liu et al, 2020 ), miR-378 (Duarte et al, 2020 ), miR-149-5p (Khan et al, 2020 ), miR-143 (Zhang L. et al, 2020 ), and miR-145 (Wang et al, 2020 ), on adipogenesis. These classic mechanisms also occur in the adipose tissue, where they have a large impact on the surrounding tissue (Arcidiacono et al, 2020 ; Raza et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Advancements to high-throughput sequencing technology has allowed deeper exploration of cellular regulatory processes (Katz et al, 2010 ). Previous studies have already revealed the regulatory effects of human miRNA, including miR-204 (Zhang Z. et al, 2020 ), miR-27a (Kim et al, 2010 ), miR-210 (Ren et al, 2020 ), miR-24 (Liu et al, 2020 ), miR-378 (Duarte et al, 2020 ), miR-149-5p (Khan et al, 2020 ), miR-143 (Zhang L. et al, 2020 ), and miR-145 (Wang et al, 2020 ), on adipogenesis. These classic mechanisms also occur in the adipose tissue, where they have a large impact on the surrounding tissue (Arcidiacono et al, 2020 ; Raza et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ese genes play various roles in biological processes in which WISP2, S100A10, and APOC1 indirectly or directly participate in lipid metabolism. WISP2 is a novel adipokine, and it has been reported that WISP2 knockdown enhanced adipogenesis [25]. S100A10 is a cell membrane repair protein holding a complex interaction relationship with the phospholipid membrane [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-425-5p [9] and miR-125a-5p [10] inhibit differentiation in Porcine intramuscular preadipocytes. bta-miR-210 positively regulates the adipogenesis of PDGFRα + cells in Bovine [11]. miR-340-5p inhibits sheep adipocyte differentiation [12].…”
Section: Introductionmentioning
confidence: 99%